Guideline: State Development Assessment Provisions : State Code 12: Development in a declared fish habitat area - Queensland. Department of National Parks, Sport and Racing. Strategic Policy and Racing Industry Governance (Brisbane, Qld. : Department of National Parks, Sport and Racing, 2017)
This document provides guidance regarding State Code 12: Development in a declared fish habitat area (FHA) of the State Development Assessment Provisions. It aims to clarify the intent of the State Development Assessment Provisions (SDAP) code and provide guidance to applicants and the community on the context of the SDAP Performance Outcomes (POs) for development in a declared Fish Habitat Area (FHA), and information that is required to support assessment of compliance with those POs.
Title from PDF cover page (viewed on August 18, 2017)
Also available online (as at 18/08/17) at https://www.npsr.qld.gov.au/managing/habitat-areas/protection-management.html.
Available online at the State Library of Queensland.
Also available online (as at 18/08/17) at https://www.npsr.qld.gov.au/managing/habitat-areas/protection-management.html.
Keywords: Fishes -- Habitat -- Queensland; Marine habitat conservation -- Queensland; Planning -- Law and legislation -- Queensland